1985
DOI: 10.1242/jcs.1985.supplement_3.16
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and overexpression of the egf receptor gene in primary human glioblastomas

Abstract: SUMMARYThe expression of epidermal growth factor (EGF) receptor in brain tumours of glial origin was studied at the protein, mRNA and genomic levels. Four out of 10 glioblastomas that overexpress EG F receptor also have gene amplification. The amplified genes appear to be rearranged, generating an aberrant mRNA in at least one of these tumours. Such receptor defects may be relevant to tumorigenesis of human glioblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 17 publications
3
93
0
Order By: Relevance
“…On the other hand, high quantities of the radiolabeled mAb can penetrate into brain tissues and can kill those antigen-negative tumor cells, which have no specific radiolabeled antibody localized on their surface. 36,37 It has been previously described that Nimotuzumab is a potent anti-cancer agent both, in vitro and in vivo by exerting a combined antiproliferative, antiangiogenic and proapoptotic activity in tumors overexpressing EGF-R. 38 This manuscript shows for the first time the results of brain tumor intracavitary radioimmunotherapy using an anti-EGF-R mAb. Previous studies using anti-EGF-R mAb administered by systemic routes have not given satisfactory treatment results, perhaps due to normal cells; mainly hepatocytes and epithelial cells, also expressing EGF-R which makes it inappropriate for treating malignant gliomas by the intravenous or intra-arterial routes.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, high quantities of the radiolabeled mAb can penetrate into brain tissues and can kill those antigen-negative tumor cells, which have no specific radiolabeled antibody localized on their surface. 36,37 It has been previously described that Nimotuzumab is a potent anti-cancer agent both, in vitro and in vivo by exerting a combined antiproliferative, antiangiogenic and proapoptotic activity in tumors overexpressing EGF-R. 38 This manuscript shows for the first time the results of brain tumor intracavitary radioimmunotherapy using an anti-EGF-R mAb. Previous studies using anti-EGF-R mAb administered by systemic routes have not given satisfactory treatment results, perhaps due to normal cells; mainly hepatocytes and epithelial cells, also expressing EGF-R which makes it inappropriate for treating malignant gliomas by the intravenous or intra-arterial routes.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have demonstrated that high-grade astrocytomas (GBMs) are characterized by ampli®cation and rearrangement of the EGF-R gene (Ekstrand et al, 1994;Libermann, et al, 1984;Steck et al, 1988;Sugawa et al, 1990;Wong et al, 1992), and overexpression of the PDGFRa and PDGFR-b receptors and their ligands (PDGF-A and PDGF-B), which are also functionally important in the molecular pathogenesis of these high-grade malignancies (Guha et al, 1995a,b;Shamah et al, 1993). Activated EGF-R and PDGF-R in astrocytoma cell lines associate with the signalling proteins Shc and GRB2, recruiting the nucleotide exchange factor mSos in proximity to the cell surface (Guha et al, 1997;Rozakis-Adcock et al, 1993), where it can exchange Ras-bound GDP for GTP resulting in activation of Ras.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic Ras mutations have not been discovered in human astrocytomas (Bos, 1989;Tuzi et al, 1991), which constitute the most common primary malignancy involving the central nervous system (Zimmerman, 1969). However, it has been demonstrated that high grade (grade IV) astrocytomas, known as glioblastoma multiforme (GBM), express high levels of ligand-dependent and -independent growth factor receptors (Fleming et al, 1992;Guha et al, 1995a;Libermann et al, 1984;Niste r et al, 1988;Steck et al, 1988;Sugawa et al, 1990;Wong et al, 1992) which are functionally relevant for tumour growth (Guha et al, 1995a,b;Shamah et al, 1993). We have demonstrated these various receptors to result in a functional activation of the Ras pathway in a wide range of astrocytoma cell lines (U87, U118, U138, U343 and U373-MG cells).…”
Section: Introductionmentioning
confidence: 99%
“…These include the well studied vulval carcinoma cell line A431 (Merlino et al, 1984). Amplification has also been described in a breast carcinoma cell line (Filmus et al, 1985) and in primary specimens of some gliomas (Libermann et al, 1984b) and squamous cell carcinomas Ozanne et al, 1986;Hunts et al, 1985). Although some bladder tumours have been reported to have high levels of EGF receptor protein expression (Neal et al, 1985;, the structure of the EGF receptor gene in bladder tumours has not been studied.…”
mentioning
confidence: 97%